Корреляционный анализ в системе мониторинга процесса налогового управления субъектами хозяйствования - Минц, А. Ю.; Лактионова, О. Е.; Mints, A. Yu.; Laktionova, O. E.; Мінц, О. Ю.; Лактіонова, О. Е. (Причорноморський науково-дослідний інститут економіки та інновацій, 2019)
В статье предложено использование методов корреляционного анализа для выявления неэффективных методов налогового управления. Корреляционный анализ применялся для оценки степени линейной зависимости между входными и выходными факторами. В качестве входных были взяты данные по НДФЛ, налоговым поступлениям в доходах местных, государственного и консолидированного бюджетов, ВВП (номинальный), уровню безработицы, минимальному ЕСВ за период 2004–2019 гг. В качестве выходных использованы статистические данные о количестве действующих предприятий различных групп. В результате использования аналитической платформы Deductor Studio получены матрицы корреляции между входными и выходными факторами, на основании которых выяснилось, что налоговая нагрузка по НДФЛ превосходит налоговую нагрузку по минимальному ЕСВ и приводит к более резкому сокращению количества субъектов хозяйствования и их работников. Вывод 1: увеличение ставки минимального ЕСВ наиболее существенно оказывает влияние на микропредприятия: их количество резко сокращается. Количество крупных предприятий менее чувствительно к росту минимального ЕСВ. Вывод 2: НДФЛ – налог, который оказывает значительное влияние на деятельность субъектов хозяйствования, особенно на малый и средний бизнес, увеличивая налоговую нагрузку налогоплательщика.

The article proposed the use of correlation analysis methods to identify inefficient methods of tax management of business entities. Correlation analysis was used to estimate the degree of linear relationship between input and output factors. As input data were taken on the tax on personal income, on tax revenues to local, state and consolidated budgets, gross domestic product (nominal), unemployment, the minimum single social contribution for the period 2004-2019. As a result of using the analytical platform Deductor Studio, matrixes of correlation between input and output factors were obtained, on the basis of which it turned out that the tax burden on the personal income tax exceeds the tax burden on the minimum unified social contribution, and leads to a sharp reduction in the number of business entities and their workers. The state should reasonably develop regulatory documents and if they impede the development of entrepreneurial activity, then it is necessary to abandon them or correct them. Existing methods of assessing the effectiveness of tax administration are not satisfied either by government agencies or taxpayers due to the fact that there is no practice of applying such techniques at all levels of government and the speed of response and adjustment of tax administration and tax policy do not meet modern requirements and are quite laborious and expensive. The correlation between input factors and the minimum unified social contribution is positive for the following of them: a) personal income tax; b) local taxes and fees; c) gross domestic product (nominal); d) revenues of the consolidated budget; e) personnel costs (large, medium, small and micro enterprises) and output field (minimum single social contribution). An inverse correlation is observed between the following input fields: a) the number of registered business entities (large, medium, small and micro enterprises); b) the number of employed and hired employees of business entities (large, medium, small and micro enterprises). Conclusion: the increase in the rate of the minimum unified social contribution has the most significant effect on micro-enterprises – their number is sharply reduced. The number of large enterprises is less sensitive to the growth of the minimum unified social contribution. The remaining factors presented as input fields for correlation with the minimum single contribution can be neglected.
Correlation analysis in the system of monitoring the process of tax management of economic entities
Keywords: промышленность; корреляция; корреляционный анализ; налоги; налоговое давление; цена; industry; correlation; correlation analysis; taxes; tax pressure; price